2018
DOI: 10.1111/jfd.12848
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus

Abstract: A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8-2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram-negative, facultative anaerobic, motile, short rod-shaped, with a length of 1.2-2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
(65 reference statements)
2
32
0
Order By: Relevance
“…It is regarded as one of the important pathogens in freshwater cultured animals (Abdolnabi, Ina‐Salwany, Daud, Mariana, & Abdelhadi, ; Baumgartner, Ford, & Hanson, ; Zhang et al, ) and has caused serious economic losses to the global aquaculture industry (Fang, Ge, & Sin, ; Hu et al, ; Ni, Wang, Liu, & Lu, ; Pridgeon et al, ; Zhang, Yan, et al, ). In addition, A. hydrophila can infect humans and cause various diseases with serious health consequences (Cascón et al, ; Fratzia, ; Liu et al, ; Sha, Kozlova, & Chopra, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as one of the important pathogens in freshwater cultured animals (Abdolnabi, Ina‐Salwany, Daud, Mariana, & Abdelhadi, ; Baumgartner, Ford, & Hanson, ; Zhang et al, ) and has caused serious economic losses to the global aquaculture industry (Fang, Ge, & Sin, ; Hu et al, ; Ni, Wang, Liu, & Lu, ; Pridgeon et al, ; Zhang, Yan, et al, ). In addition, A. hydrophila can infect humans and cause various diseases with serious health consequences (Cascón et al, ; Fratzia, ; Liu et al, ; Sha, Kozlova, & Chopra, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms rarely occur with other Aeromonas infections. This observation implied that A. schubertii pathogenesis was distinct from common Aeromonas species [ 9 ]. Nodule formation has traditionally been considered a dangerous strategy by which to limit infection, protecting the host by walling off resistant pathogens [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, A. schubertii has been reported to be the causative agent for outbreaks of “white spots disease” in snakehead fish: C. argus [ 6 ], C. maculata [ 7 ], and the hybrid snakehead [ 8 ]. The typical symptoms of the disease are severe multiple white nodules scattered throughout the spleen, liver, and kidney [ 6 , 9 ]. The disease has a high mortality rate of approximately 45%, resulting in serious economic loss, which jeopardizes the development of snakehead aquaculture [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of S. dysgalactiae may be related to the fish species, developmental stage, size and so on. Previous researches indicated that that the lethal concentration of Aeromonas hydrophila to different fish species was a large range (Santos et al, ), and the pathogenicity of Aeromonas schubertii to tilapia and zebrafish was also quite different (Liu et al, ). In addition, the virulence factors and genetic characteristics of isolate F3 may be different from the strain isolated from tilapia (Netto et al, ).…”
Section: Discussionmentioning
confidence: 99%